KAPASITAS PENANGKAPAN BERLEBIH DAN TANGKAP LEBIH PERIKANAN SKALA KECIL DI KOTA SEMARANG - Jamaludin Malik; Achmad Fahrudin; Dietriech Geoffrey Bengen; Taryono Khodiron (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Fisheries in Semarang City are dominated by small-scale fisheries. This is indicated by the use of the largest fishing fleet of 10 gross tons operating near the coast. This study aims to analyze the status of small-scale fisheries in Semarang City for sustainable management. Sustainable management is management that guarantees the availability of natural resources and environmental services for future generations. The study was conducted for three months, namely September-November 2018 in the coastal waters of Semarang City, which was part of the Fisheries Management Region (WPP) 712. The method used in this study is the analysis of time series surplus production, namely data from the catch (ton/year) and the number of fishing gear (unit) within 10 years (2007-2016), to calculate the catch per-unit effort (CPUE), maximum sustainable yield (MSY), optimum effort (fopt), utilization rate (TP) and capacity level (TK). This study was obtained results of a downward trend in CPUE; the existing fishery catch or production in 2016 has exceeded the MSY value is 479 tons/year (Schaefer) and 439.11 tons/year (Fox); utilization rate of more than 100% which is 108-127% (Schaefer) and 118-138% (Fox), so that small-scale fisheries in Semarang City are at the level of over-exploited. Based on the fopt analysis, the number of fishing gear used (fexisting) has exceeded the optimum effort with a fishing capacity exceeding 100%, so that small-scale fisheries in Semarang City have experienced overcapacity.